Novel polymorphisms in the equine FSH receptor (eFSHR) gene and their association with embryo production following artificial insemination in quarter horse mares - Roberta A. SIlva; Moises L. Moreira; Elem }ز Barra; Priscilla C. Ramos; Lawrence O. Barros; Gustavo F. Carneiro; Elizabeth M. Barbosa; Sebastião T. Rolim Filho; Ednaldo S. Filho (Iraqi Journal of Veterinary Sciences)
The quarter horse is a breed that stands out for its strength, explosiveness, versatility, and use in several equestrian sports. For equines, assisted reproduction presents challenges for artificial insemination and/or in vitro fertilization. This study aimed to characterize a portion of the eFSHR gene promoter in Quarter Horses and associate it with the number of embryos produced in the 2021 season. Peripheral blood samples were collected from 92 inseminated mares for several embryos produced, DNA extraction, followed by conventional PCR, purification, and sequencing using the Sanger method. Genetic population parameters and potential binding factor sites were determined. The association of haplotypes with the number of embryos produced was analyzed using the PROC MIXED of SAS (onDemand) with a significance level of 0.05. Three single nucleotide polymorphisms (SNPs) were identified: -217G>T, -195G>A, and 127A>G. Four haplotypes were determined: G/G/A, G/G/G, G/G/GA, and G/GA/G. The wild-type sequence had 74 binding sites, with Sp1 and TFAP-2alpha binding at position -217 and GR binding at position 195. The mutant sequence had 71 identified sites. The eFSHR gene promoter demonstrated polymorphism in Quarter Horses, but there was no association with the number of produced embryos. However, it could be used for other reproductive traits in mares.